2002
DOI: 10.2741/armulik
|View full text |Cite
|
Sign up to set email alerts
|

Splice variants of human b1 integrins: origin, biosynthesis and functions

Abstract: The integrin beta1 subfamily of adhesion receptors consists of 12 members and forms the biggest subfamily among integrins. Human integrin subunit beta1 has five cytoplasmic splice variants (beta1A, beta1B, beta1C-1, beta1-C2, beta1D). Even though cytoplasmic splice variants do not change the ligand-specificity of a beta1 integrin, clustering of these different splice variants triggers signaling pathways that lead to a different cellular response. The main focus of this review is on the origin and specific func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Integrin signaling is facilitated through respective types of splice variants expressed (Sakai et al, 1998;Armulik, 2002). Two splice variants in the b1-integrin cytoplasmic domains, b1A and b1D, display two conserved NPxY motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Integrin signaling is facilitated through respective types of splice variants expressed (Sakai et al, 1998;Armulik, 2002). Two splice variants in the b1-integrin cytoplasmic domains, b1A and b1D, display two conserved NPxY motifs.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the largest subfamily of integrins share β1 as the common β‐subunit. The cytoplasmic domains of β1A and β1D splice variants (Armulik, 2002) each contain two conserved NPXY motifs. These motifs are utilized for several interactions, and their involvement in the inside‐out activation of integrins (Pfaff et al , 1998; Calderwood & Ginsberg, 2003; Tadokoro et al , 2003) as well as in the regulation of FAK activation (Wennerberg et al , 2000) has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Integrins containing the β1B splice form, which lacks the carboxy‐terminal half of β1A including the NPXY motifs, are in an inactive conformation and cannot bind the normal β1‐integrin ligands. The β1B variant has no apparent physiologic function and probably arises through a splicing error (Armulik, 2002). Such integrins can, however, mediate cell adhesion to anti‐integrin IgG and the bacterial protein invasin without inducing FAK activation (Armulik et al , 2000; Gustavsson et al , 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Alternative splicing of mRNA from several integrin subunit genes is known to produce different proteins [20][21][22][23][24][25][26][27]. To be inclusive of all the integrin messages, we intentionally selected exons that were not alternatively spliced in the above-mentioned expression study using the four sets of primers (I-IV).…”
Section: Detection Of Differential Splicing Of Selected Integrin Genementioning
confidence: 99%